ID 227 – Evidence-based modelling of nociceptive laser-evoked potentials. Issue 3 (March 2016) - Bradley, C.; Perchet, C.; Bastuji, H.; Garcia-Larrea, L.
Abstract : To this day, source modelling of EEG responses to nociceptive stimulation has relied on interplay between physiological hypotheses and pure mathematical estimates. Here, we propose to refine the models by integrating current knowledge in multi-modal brain imaging (fMRI and intracranial EEG) into nociceptive EEG responses modelling. We recorded laser-evoked potentials to right hand stimulation in 15 healthy participants, using high-density EEG (128 electrodes) and modeled sources during the first second of brain activity in BESA. Initial dipolar source position was defined by converging data from SEEG and fMRI. Grand-average data was well explained by a 7-dipole model. For 5 dipoles, source activity peaked ∼200 ms after laser stimulation (right and left posterior insula-medial operculum, right frontal, left somatosensory-motor, anterior cingulate cortex). Left frontal dipole had a later, less defined peak, while the posterior cingulate dipole was maximally active ∼400 ms. Overall, even though the model was constrained regarding dipole position, activity time-course was coherent with current knowledge. Notably, the most posterior dipole, located in regions traditionally linked to self-perception, was active late in the interval. Even though this model remains probably incomplete and might be furthered by the use of higher electrode densities, it demonstrates the potential of integrating multi-modal neuro-imaging data.